Learning Joomla! 1.5 extension development : creating modules, components, and plug-ins with PHP : a practical tutorial for creating your first Joomla! 1.5 extensions with PHP /: creating modules, components, and plug-ins with PHP : a practical tutorial for creating your first Joomla! 1.5 extensions with PHP. (2007) - Unknown
No abstract available